2007
DOI: 10.1186/1471-230x-7-41
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with the presence of non alcoholic fatty liver disease in an apparently healthy adult population in primary care units

Abstract: Background: Fatty liver disease is characterized by the accumulation of fat vacuoles inside of the hepatocytes. Non alcoholic fatty liver is associated with obesity, type 2 diabetes, dyslipemia, the intake of certain drugs and with the so-called metabolic syndrome. However, there is little information on the clinical relevance of this disorder as a healthcare problem in the general population, since the studies published generally include a limited number of patients and the diagnosis is established on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
4
27
0
4
Order By: Relevance
“…Nonetheless, the frequency of NAFLD (26%) identified in our study is within the wide range (14-34%) previously reported in general population studies carried out in Italy, 118 Spain, 120 Asia 121 and America. 122 The variation in reported frequencies may be influenced by ethnic diversity 122,130 and differences in study methodologies.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Nonetheless, the frequency of NAFLD (26%) identified in our study is within the wide range (14-34%) previously reported in general population studies carried out in Italy, 118 Spain, 120 Asia 121 and America. 122 The variation in reported frequencies may be influenced by ethnic diversity 122,130 and differences in study methodologies.…”
Section: Discussionsupporting
confidence: 53%
“…The prevalence of NAFLD has risen markedly to 14-34% of the general population in Europe, 119,120 Asia 121 and America 122 in recent years. Although patients with simple NAFLD are believed to have benign disease, there is now clear evidence that those who have progressed to NASH and fibrosis are at a much higher risk of developing hepatocellular carcinoma (HCC), liver failure and death.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation is the diagnosis of NAFLD by abdominal echography. Despite echography being a good diagnostic method, it is not useful for diagnosing liver fat when its presence represents less than 30% of the liver volume [4,5,8,9,15,36], or in cases of morbid obesity [37].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol of the main characteristics of the study has been published earlier [15]. This was a transversal, multicentre study with a populational base of adult individuals ascribed to 25 primary healthcare centres in the area of Barcelonès Nord i Maresme (Catalonia, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays NAFLD has become a major public health hazard worldwide. The prevalence rates range from 24% to 42% in Western countries and 5% to 40% in Asian countries [12][13][14]. Hispanics having the highest prevalence (45-58%), followed by Caucasians (33-44%) and African Americans (24-35%) [15][16].…”
Section: Discussionmentioning
confidence: 99%